Desenvolvimento, caracterização e avaliação in vitro de cimento ósseo à base de nano hidroxiapatitas substituídas com magnésio, estrôncio e zinco. - Alexa Magalhães Dias (2020)
The incorporation of ions into the HA lattice can affect its structure, crystallinity, solubility and cytotoxicity. From the ions present in the composition of bone apatite, Mg2+, Sr2+ and Zn2+ are recognized for promoting angiogenesis and osteogenesis. The substituted HAs can be present better bioactivity for supplying ions with potential to stimulate bone neoformation in grafted sites. This study described the synthesis, characterization and comparison of a range of substituted and co-substituted nHAs contained Sr2+, Mg2+ or Zn2+. Then, it developed bone cement based on HAs with better cytotoxicity results, associated with DCPA, gelatin and chitosan. The nHAs were physicochemically characterized using different techniques. The co-precipitation method was effective for synthesizing HAs with nanometric dimensions. Compared to pure nHA, the diffractograms, FTIR spectra and lattice parameters of the substituted and co-substituted nHAs showed changes, indicating that the incorporation of cations resulted in distortions of the HA lattice. MTT tests demonstrated that the all synthesized nHAs were not cytotoxic after direct contact with fibroblasts (L929) and pre-osteoblasts (MC3T3) cultures. MTT results suggest that Mg2+/Sr2+ and Zn2+/Sr2+ co-substituted nHAs seem to induce more proliferation of fibroblastic and osteoblastic than pure and Mg2+, Sr2+ and Zn2+ substituted nHAs. Bone cements developed showed self-hardening and washout resistance. Also, they Exhibited high wettability and ion release profile with non-toxic concentrations of Ca2+, Sr2+, Mg2+ and Zn2+, range within indicated doses to stimulate the proliferation of osteoblasts. The cement exhibited excellent in vitro cytocompatibility in fibroblastic, endothelial and osteoblastic cell cultures. Cement containing Mg2+/Sr2+ co-substituted nHAs showed better results of the cell viability. After 24 hours of indirect contact with L929 fibroblast culture, the cell growth in the C2 group was highest than all study groups (P <0.01). In EA.hy926 endothelial culture, the cell viability of the C3 group was significantly highest than all other groups after 24 hours (p <0.001). The indirect cytotoxicity in MC3T3 pre-osteoblastic culture revealed that after 48 hours, the C3 group showed the greatest cell viability than all the study groups (p <0.01). The tube formation assay suggests that all cement have angiogenic potential, being that the cements containing Zn2+ / Sr2+ co-substituted nHAs exhibited significantly better results (p < 0,001). Despite being necessary to perform a more significant number of biocompatibility tests, the incorporation of ions into the nHA lattice, which are recognized for affects angiogenesis and osteogenesis, may have resulted in the development of bone cements with the potential to promoting bone regeneration.